Permeability Coefficients of Murine Enterocyte Membranes for Water and Cryoprotectants - Ogurtsova, Viktoriya V.; Kovalenko, Svetlana Ye.; Kovalenko, Igor F.; Gordiyenko, Olga I. (Problems of Cryobiology and Cryomedicine, 2016)
Osmotic response of cells and transport properties of membrane are essential for cryobiological research in terms of choosing the optimal conditions to cryopreserve the specific cell type. In the present study we have found the permeability coefficients of murine enterocytes to water and such cryoprotectants as: ethylene glycol (EG), glycerol, 1,2-propanediol (1,2-PD) and dimethyl sulfoxide (DMSO). The experimental time dependencies of cell volume revealed during their contact with hypertonic solutions of cryoprotectants were fitted with numeric solutions of nonlinear equations describing this dependence in terms of linear thermodynamics of irreversible processes. The found filtration coefficients had no significant differences in cryoprotectant solutions of 1,2-PD, DMSO and glycerol ((1.42; 1.3; 1.24)x10–14 m3/N·sec, respectively) and were almost twice higher in EG solution (2.4)x10–14 m3/N·sec). The membranes of murine enterocytes showed the highest penetration rate for EG 4.79x10–7 m/s which was probably due to its negative effect on enterocyte membranes. Permeability coefficient for 1,2-PD, DMSO and glycerol was (0.672; 0.530; 0.134)x10–7 m/s, respectively. The obtained data can be used in selection of the most proper regimen of cryopreservation for these cells. Probl Cryobiol Cryomed 2016; 26(3): 221–228